2016
DOI: 10.1155/2016/7968201
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Biliary Drainage in Cases of Borderline Resectable Pancreatic Cancer Treated with Neoadjuvant Chemotherapy and Surgery

Abstract: Objective. To elucidate the optimum preoperative biliary drainage method for patients with pancreatic cancer treated with neoadjuvant chemotherapy (NAC). Material and Methods. From January 2010 through December 2014, 20 patients with borderline resectable pancreatic cancer underwent preoperative biliary drainage and NAC with a plastic or metallic stent and received NAC at Hiroshima University Hospital. We retrospectively analyzed delayed NAC and complication rates due to biliary drainage, effect of stent type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 30 publications
1
49
1
Order By: Relevance
“…[18][19][20] The roles of biliary decompression, drainage method, and choice of the biliary stent during NAC/NACRT are very significant during the preoperative period. The retrospective study by Tsuboi et al 21 revealed that MS implantation is effective for preoperative biliary drainage in pancreatic cancer cases treated with NAC because of the low rates of stent-related complications (0% vs NACRT, neoadjuvant chemoradiotherapy; RDI, relative dose intensity; RBO, recurrent biliary obstruction; ES, endoscopic sphincterotomy; AE, adverse event; SSPPD, subtotal stomach-preserving pancreaticoduodenectomy; TP, total pancreatectomy; IQR, interquartile range. *First part with S-1 with radiotherapy; † Second part with gemcitabine; ‡ The size measured on contrast-enhanced computed tomography within 2 weeks before pancreatoduodenectomy; § Theoretical cost calculated by stent value, stenting number, procedure and admission cost; ΙΙ Abdominal pain after stenting.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] The roles of biliary decompression, drainage method, and choice of the biliary stent during NAC/NACRT are very significant during the preoperative period. The retrospective study by Tsuboi et al 21 revealed that MS implantation is effective for preoperative biliary drainage in pancreatic cancer cases treated with NAC because of the low rates of stent-related complications (0% vs NACRT, neoadjuvant chemoradiotherapy; RDI, relative dose intensity; RBO, recurrent biliary obstruction; ES, endoscopic sphincterotomy; AE, adverse event; SSPPD, subtotal stomach-preserving pancreaticoduodenectomy; TP, total pancreatectomy; IQR, interquartile range. *First part with S-1 with radiotherapy; † Second part with gemcitabine; ‡ The size measured on contrast-enhanced computed tomography within 2 weeks before pancreatoduodenectomy; § Theoretical cost calculated by stent value, stenting number, procedure and admission cost; ΙΙ Abdominal pain after stenting.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of neoadjuvant therapy, an RCT (54 patients) found that use of FCSEMSs resulted in a longer stent patency duration and fewer days of delay in neoadjuvant therapy compared with plastic stents and uncovered SEMSs; total costs associated with PBD were similar for all stent models [27]. Similarly, two retrospective studies (total, 72 patients) found that, compared with SEMSs, plastic stents were associated with more complications; one of the studies also analyzed the delay in neoadjuvant therapy and costs: with SEMSs, the delay was shorter and the total costs were similar [28,29]. The type of SEMS was stated in one study only (FCSEMS) [29].…”
Section: Preoperative Biliary Drainagementioning
confidence: 93%
“…Endoscopic placement of a self-expandable metallic stent (SEMS) is the standard treatment for distal MBO in patients with unresectable (UR) PC due to the long stent patency compared to plastic stents 13 14 . Even for patients with BR or R PC who have a prolonged time to surgery, preoperative biliary drainage is considered essential, and several studies have reported the efficacy of SEMS placement in this setting 15 16 17 18 19 20 .…”
Section: Introductionmentioning
confidence: 99%